Association between Neutrophil to Lymphocyte Ratio and Post Operative Atrial Fibrillation after Coronary Artery Bypass Graft operation. - Sidiek, Aboesina; Herry, Yan; Ardhianto, Pipin; Bahrudin, Udin (Journal of Biomedicine and Translational Research, 2024)
ABSTRACT Background: Post operative atrial fibrillation (POAF) is associated with cardiovascular outcomes such as stroke, heart failure, and mortality. Neutrophil to lymphocyte ratio (NLR) is one of biomarker of inflammation. The use of cor pulmonary bypass(CPB), surgical trauma and reperfusion injury during cardiac surgery causes inflammation. NLR is suspected to be a biomarker that represents the inflammatory response as a modulator of POAF, but data are still lacking.This study analyzed the association between NLR and POAF after coronary artery bypass graft (CABG) operation.Methods: This was an Observational analytic study, involving patients after the CABG procedure in Kariadi Hospital between June 2022 to September 2023. NLR was assessed in the first three hours after operation. ECG Holter was attained for 96 hours post-CABG procedure.Results: The total subject was 62 patients, consisting of 57 men and 5 women with a mean age of 58,7 ± 6.39 years. Mean postoperative NLR 4.95 ± 2.17 with a median of 4.56 (1.52-11.00). There was a significant association between post-operative NLR with POAF after CABG (p=0.006, OR 4.64, 95%CI 1.50-14.35). High inotropic dose and β blocker initiation time less than 45 hours correlate significantly with POAF after CABG (p<0.001, OR 6.94 dan p=0.001, OR 0.17).Conclusions: Postoperative NLR is associated significantly with POAF after CABG. Keywords: Neutrophil to Lymphocyte Ratio, Post Operative Atrial Fibrillation, coronary artery bypass graft, ECG Holter